PERAN GURU DALAM MENGATASI KESULITAN BELAJAR SISWA - Laia, Tuhosokhi (Universitas Nias Raya, 2024)
This research was motivated by students' lack of understanding of the material taught by the teacher. The purpose of this study is to describe the role of teachers in overcoming student learning. This type of research is a type of qualitative research with a descriptive approach. The results of the study found were the role of teachers in overcoming the learning difficulties of grade XI students of SMA Negeri 1 Amandraya that had played an active and effective role through motivation, facilitators, class managers and supervisors. This role of the teacher can help students on learning difficulties by providing understanding to their students. Suggestions: 1. It is recommended for the school to pay more attention to students who have difficulty in understanding learning, especially if the student is an outstanding student, perhaps with cooperation between the school such as the principal, teachers, staff and parents together to provide solutions or solutions to help overcome student learning difficulties. 2. For teachers, especially teachers of economics subjects, it is expected to further increase their role in overcoming student learning.